2005
DOI: 10.1590/s1516-35982005000700039
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão, digestibilidade das rações e produção de leite em cabras Saanen submetidas a diferentes relações volumoso: concentrado na ração

Abstract: RESUMO -Objetivou-se avaliar o desempenho produtivo, os parâmetros sangüíneos e a digestibilidade dos nutrientes em cabras Saanen no início e após 60 dias de lactação. Foram utilizadas 20 cabras (59,59 kg ± 6,97) em delineamento inteiramente casualizado, submetidas a diferentes relações volumoso:concentrado nas rações (40:60, 50:50, 60:40, 70:30 e 80:20), correspondendo a 2,95; 2,83; 2,70; 2,58 e 2,46 Mcal de EM/kg MS, respectivamente. Os animais permaneceram confinados em baias individuais, com controle diári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
1
7
0
5
Order By: Relevance
“…This explains the largest FE values observed in postpartum, when the level of DMI is lower. Zambom et al (2005b) also observed higher values for FE in early lactation, with a decrease at 60 days in milk, but with a positive linear effect of increasing dietary energy. Oliveira Jr. et al (2002) observed that lactating Alpine goats fed soybeans increased their FE by 24%.…”
Section: Discussionmentioning
confidence: 71%
“…This explains the largest FE values observed in postpartum, when the level of DMI is lower. Zambom et al (2005b) also observed higher values for FE in early lactation, with a decrease at 60 days in milk, but with a positive linear effect of increasing dietary energy. Oliveira Jr. et al (2002) observed that lactating Alpine goats fed soybeans increased their FE by 24%.…”
Section: Discussionmentioning
confidence: 71%
“…Existem na literatura diversos trabalhos visando estabelecer o nível ótimo de volumoso em relação ao nível de concentrado em dietas para cabras leiteiras (Kawas et al, 1991;Hussain et al, 1996;Silva et al, 1999;Gonçalves et al, 2001;Goetsch et al, 2001;Zambom et al, 2005), mas os resultados são os mais variados possíveis. O consumo médio de 1,95 kg/dia de MS encontrado neste estudo foi um pouco elevado em comparação ao relatado pelo AFRC (1998), uma vez que, para animais produzindo 2 litros de leite, pesando 40 kg de peso vivo, recomenda-se 1,60 kg/dia de MS, o que indica a possibilidade do uso de níveis mais elevados de feno em dietas para cabras Moxotó.…”
Section: Resultsunclassified
“…Three scientific articles (Oliveira Jr. et al, 2002;Zambom et al, 2005;Branco et al, 2011) were used to analyze the influence of 3.5%-fat corrected milk yield on feed efficiency, with 14 treatments and 81 experimental units. Four studies were used for the dry matter digestibility, consisting of one doctoral thesis and three scientific articles (Silva, 2005;Fonseca et al, 2008;Zambom et al, 2008;Branco et al, 2011), totaling 16 treatments and 83 experimental units.…”
Section: Methodsmentioning
confidence: 99%
“…For the NDF levels, three studies were used: one doctoral thesis and two scientific articles (Carvalho et al, 2006;Branco et al, 2011;Felisberto, 2011), totaling 14 treatments and 51 experimental units. For the roughage: concentrate ratio, two scientific articles were used (Silva et al, 1999;Zambom et al, 2005), with eight treatments and 38 experimental units. One doctoral thesis (Felisberto, 2011) was used for body weight, totaling four treatments and 16 experimental units.…”
Section: Methodsmentioning
confidence: 99%